On certainty and other philosophical essays on cognition. - Rescher, Nicholas (De Gruyter, 2011)
On Certainty continues Rescher's longstanding practice of publishing occasional studies that form part of a wider program of investigation of the scope and limits of rational inquiry in the pursuit of understanding. And pragmatism forms a subtextual Leitmotiv of these essays, seeing that the linking idea at work throughout is that knowledge is a tool for the management of our theoretical and practical affairs, and that what we ask of it is serviceability for the uses we have in view.
Keywords: Cognition -- Philosophy.; Cognition -- Philosophie.; PHILOSOPHY -- Metaphysics.; Cognition -- Philosophy